Pemanfaatan Sampah Rumah Tangga untuk Pupuk Organik di Desa Sukalaksana: Utilization of Household Waste for Organic Fertilizer in Sukalaksana Village - Hilmiana, Hilmiana; Kirana, Desty Hapsari (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2025)
This study is part of a Community Service Program (PKM) aimed at evaluating the effectiveness of household waste composting into liquid organic fertilizer as a sustainable solution for waste management. Conducted in Sukalaksana Village, the program involved the community through education, training, and mentoring to enhance awareness and skills in managing organic waste. Data were collected through interviews and focused group discussions, as well as measurements of the volume of processed waste and the resulting liquid fertilizer. The findings indicate that composting significantly reduces waste volume and produces high-quality liquid organic fertilizer, although the program's success depends on community awareness and the availability of adequate infrastructure. The program concludes that household waste composting is an effective approach to supporting sustainable agriculture and environmental preservation, with recommendations to enhance community education and develop infrastructure to enable broader adoption of this practice.